Essentials of psychiatric mental health nursing : concepts of care in evidence-based practice - Townsend, Mary C., 1941- 4 0 16; 5 (Philadelphia : F.A. Davis Company, 2008)
Accompanying CD-ROM contains an Electronic Test Bank with 300 NCLEX-style questions, Student workbook -- Links to online resources: Animated drug pathways for the neurobiological brain images ; Care plans ; Concept map care plan template ; Sample client teaching guide ; Interactive learning activities ; Meet the author
Mental health and mental illness -- Concepts of personality development -- Biological implications -- Ethical and legal issues -- Cultural and spiritual concepts relevant to psychiatric/mental health nursing -- Relationship development and therapeutic communication -- The nursing process in psychiatric/mental health nursing -- Milieu therapy : the therapeutic community -- Intervention in groups -- Intervening in crises -- Psychopharmacology -- Complementary and psychosocial therapies -- Delirium, dementia, and amnestic disorders -- Substance-related disorders -- Schizophrenia and other psychotic disorders -- Mood disorders -- Anxiety disorders -- Anxiety-related disorders -- Disorders of human sexuality -- Eating disorders -- Personality disorders -- Children and adolescents -- Victims of abuse or neglect -- The aging individual -- Community mental health nursing -- The bereaved individual -- Appendix A : DSM-IV-TR classification : Axes I and II categories and codes -- Appendix B : NANDA nursing diagnoses : taxonomy II domains, classes, and diagnoses -- Appendix C : assigning nursing diagnoses to client behaviors -- Appendix D : mental status assessment
Includes bibliographical references and index
System requirements for accompanying CD-ROM: OS Windows 2000/XP/Vista
Keywords: 2 -- 0; 6; Psychiatric nursing -- 20; 20; 2